ELDERLY PERCEPTIONS ON TRAVELING IN DIGITAL ERA - Kusumaningrum, Dewi Ayu; Tany, Nelsen (International Conference on Cultural Studies; Vol 2 (2019): Proceedings International Conference on Cultural Studies, 2019)
Digitalization of tourism offers convenience for the tourist, especially for elderly tourists. Segmentation of Indonesian elderly tourists is quite dynamic, is expected to experience rapid growth compared to other tourist market segments. Some elderly tourists even feel they are younger than their age because of improved health, and they are more active. The purpose of the research is to find out the perceptions of the elderly in traveling in the digital era. Quantitative descriptive research method. The technique of collecting data uses a questionnaire. Analysis by calculating the percentage perception index, classifies in the criteria interval the assessment categories. Research results: 1) Perception of the assessment factors 3.3132 (82.82%) including the High category. The attitudes, interests and expectations of high-aged tourists, as active internet users, feel comfortable in finding information from the internet. 2) Perception of situation factors 3.3825 (84.56%) including the Very High category. Have plenty of free time to find information on tourist attractions, the state of facilities. 3) Perception of the target factor of 3.4216 (85.54%) including the Very High category. Tourist attractions traced through the internet use technology, so that elderly tourists can see the uniqueness, level of comfort, security in accordance with reality.